1993
DOI: 10.1177/088307389300800207
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem and Cerebellar Vermis Involvement in Autistic Children

Abstract: Recent reports have suggested functional abnormalities of the brain stem in autistic children, and structural abnormalities have also been reported. We obtained magnetic resonance imaging (MRI) scans for 21 autistic children and compared them with 21 control MRI scans. The areas of the brain stem and cerebellar vermis were measured using midsagittal images. The brain stem and cerebellar vermis lobules VIII to X were found to be significantly smaller in autistic children. A positive correlation between the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 27 publications
4
47
0
2
Order By: Relevance
“…The most consistent finding has been that brain volume appears to be larger in autism [23-26], although there is emerging consensus that this finding is restricted to young children with autism [27,28]. Differences in cerebellar volume are reported in many studies [15-17,29-34], but the directionality of the finding in autism (larger or smaller relative to comparison group) and region within the cerebellum (vermis or hemisphere) differ greatly between studies. Most studies of the cerebellum, however, report reduced vermal volume in autism, unless IQ is matched or covaried in the analysis (e.g., see [12] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…The most consistent finding has been that brain volume appears to be larger in autism [23-26], although there is emerging consensus that this finding is restricted to young children with autism [27,28]. Differences in cerebellar volume are reported in many studies [15-17,29-34], but the directionality of the finding in autism (larger or smaller relative to comparison group) and region within the cerebellum (vermis or hemisphere) differ greatly between studies. Most studies of the cerebellum, however, report reduced vermal volume in autism, unless IQ is matched or covaried in the analysis (e.g., see [12] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal findings in the posterior fossa structures described in autistic patients include hypoplasia of lobules VI and VII of the cerebellar vermis and brainstem hypoplasia. [34][35][36] Abnormal cerebellar findings were not properly reproduced and some researchers believe they may be related to technical and methodological factors. 37,38 Courchesne et al performed a meta-analysis including data from various laboratories and suggested a bimodal distribution of the measures of cerebellar vermis in investigated autistic patients.…”
Section: Neuropathology and Neuroimagingmentioning
confidence: 99%
“…3 Structural and functional changes have been reported in the brains of children with autism, 4 attention deficit disorder, 5 developmental dysphasia, 6 obsessive compulsive disorder, 7 schizophrenia, 8 and an increased prevalence of birth complications 9 and viral illnesses during pregnancy 10 have been associated with risk of later schizophrenia.…”
mentioning
confidence: 99%